Efficacy and Safety of Endoscopic Full-Thickness Resection in the Colorectum: Results From the German Colonic FTRD Registry. (21st December 2020) - Meier, Benjamin; Stritzke, Bettina; Kuellmer, Armin; Zervoulakos, Philipp; Huebner, Georg Hermann; Repp, Michael; Walter, Benjamin; Meining, Alexander; Gutberlet, Klaus; Wiedbrauck, Thomas; Glitsch, Anne; Lorenz, Albrecht; et al.
Abstract : INTRODUCTION: Endoscopic full-thickness resection (EFTR) is a powerful option for resection of colorectal lesions not amenable to conventional endoscopic resection. The full-thickness resection device (FTRD) allows clip-assisted EFTR with a single-step technique. We report on results of a large nationwide FTRD registry. METHODS: The "German colonic FTRD registry" was created to further assess efficacy and safety of the FTRD System after approval in Europe. Data were analyzed retrospectively. RESULTS: Sixty-five centers contributed 1, 178 colorectal FTRD procedures. Indications for EFTR were difficult adenomas (67.1%), early carcinomas (18.4%), subepithelial tumors (6.8%), and diagnostic EFTR (1.3%). Mean lesion size was 15 × 15 mm and most lesions were pretreated endoscopically (54.1%). Technical success was 88.2% and R0 resection was achieved in 80.0%. R0 resection was significantly higher for subepithelial tumor compared with that for other lesions. No difference in R0 resection was found for smaller vs larger lesions or for colonic vs rectal procedures. Adverse events occurred in 12.1% (3.1% major events and 2.0% required surgical treatment). Endoscopic follow-up was available in 58.0% and showed residual/recurrent lesions in 13.5%, which could be managed endoscopically in most cases (77.2%). DISCUSSION: To date, this is the largest study of colorectal EFTR using the FTRD System. The study demonstrated favorable efficacy and safety for "difficult-to-resect" colorectal lesions and confirms results of previous studies in a large "real-world" setting. Further studies are needed to compare EFTR with other advanced resection techniques and evaluate long-term outcome.